Prevalence study of Legionella spp. contamination in ferries and cruise ships - Masia Maria; Deriu Maria; Dettori Marco; Sotgiu Giovanni; Piana Andrea; Azara Antonio; Are Bianca; Muresu Elena (BMC, 2006)
Abstract Background In the last years, international traffic volume has significantly increased, raising the risk for acquisition of infectious diseases. Among travel-associated infections, increased incidence of legionellosis has been reported among travellers. Aim of our study was: to describe the frequency and severity of Legionella spp. contamination in ferries and cruise ships; to compare the levels of contamination with those indicated by the Italian ministerial guidelines for control and prevention of legionellosis, in order to assess health risks and to adopt control measures. Method A prevalence study was carried out on 9 ships docked at the seaports of northern Sardinia in 2004. Water samples were collected from critical sites: passenger cabins, crew cabins, kitchens, coffee bars, rooms of the central air conditioning system. It was performed a qualitative and quantitative identification of Legionella spp. and a chemical, physical and bacteriological analysis of water samples. Results Forty-two percent (38/90) water samples were contaminated by Legionella spp.. Positive samples were mainly drawn from showers (24/44), washbasins (10/22). L. pneumophila was isolated in 42/44 samples (95.5%), followed by L. micdadei (4.5%). Strains were identified as L. pneumophila serogroup 6 (45.2%; 19 samples), 2-14 (42.9%), 5 (7.1%) and 3 (4.8%). Legionella spp. load was high; 77.8% of the water samples contained > 104 CFU/L. Low residual free chlorine concentration (0-0,2 mg/L) was associated to a contamination of the 50% of the water samples. Conclusion Legionella is an ubiquitous bacterium that could create problems for public health. We identified Legionella spp. in 6/7 ferries. Microbial load was predominantly high (> 104 CFU/L or ranging from 103 to 104 CFU/L). It is matter of concern when passengers are subjects at risk because of Legionella spp. is an opportunist that can survive in freshwater systems; high bacterial load might be an important variable related to disease's occurrence. High level of contamination required disinfecting measures, but does not lead to a definitive solution to the problem. Therefore, it is important to identify a person responsible for health safety in order to control the risk from exposure and to apply preventive measures, according to European and Italian guidelines.